A comparison of the costs of laparoscopic myomectomy and open myomectomy at a teaching hospital in southern Taiwan - Chi-Chang Chang (Elsevier, 2013)
Objective: To compare the costs of traditional open myomectomy (OM) with laparoscopic myomectomy (LM). Materials and Methods: A retrospective review was conducted of the medical records of 155 women who underwent traditional open myomectomy (OM) or laparoscopic myomectomy (LM) in a teaching hospital in Taiwan. Results: The total medical service expense and the patient out-of-pocket expense were significantly higher for women who received LM than for women who received OM. However, the operative time and blood loss during surgery were significantly less in women who received LM than in women who received OM. Conclusion: The overall expense is higher for LM than for OM; however, the laparoscopic approach has numerous advantages for patients, including shorter operative time, less blood loss, and a more rapid recovery time. No difference existed in the rate of complications or in the recurrence of disease for the two procedures.